Neurological manifestations of Covid-19: a literature review (Research, Society and Development, 2022)
This article aimed to analyze the research published so far on the neurological symptoms of Covid-19 and present the main results observed, in order to provide a greater understanding of the broad dimension of the disease and, thus, contribute to the identification of this symptomatology occur in a timely manner. This is an integrative literature review, guided by scientific articles indexed in the Google Academic database, National Library of Medicine (PubMED), Latin American and Caribbean Literature in Health Sciences (LILACS) and Scientific Electronic Library Online (SciELO), between the years 2020 and 2021. For this purpose, the descriptors "manifestations", "neurological", "Covid-19" and their respective counterparts in English and Spanish were used. In the literature, definitive conclusions are lacking about the time of onset of neuro-Covid manifestations, as well as which ones are more severe. Furthermore, the prognosis of this condition remains uncertain. Regarding the frequently reported symptoms, there was a predominance of stroke (6.0% - 74.0%), headache (9.0% - 72.0%), dysgeusia (5.6% - 41.0%), anosmia (5.1% - 41.0%), altered level of consciousness (31.0% - 39.0%) and seizure (5.0% - 29.7%). Guillain-Barré syndrome, meningitis, and myelopathy were uncommon diagnoses. The initial identification of neurological disorders comes from correctly performed anamnesis and physical examination, and, once the diagnosis is established, the correct management of the patient becomes essential, and, although there is no specific treatment for neurological symptoms, support measures and certain pharmacological therapies have been adopted for the care of the diseased.